Tuning glucose decomposition in hot-compressed gamma-valerolactone/water mixtures: From isomerization to dehydration reactions - Song, B.; Yu, Yun; Wu, Hongwei (Elsevier Ltd, 2019)
This study reports the reaction mechanism and kinetics of glucose hydrothermal decomposition in hot-compressed gamma-valerolactone(GVL)/water (HCGW) at 175–225 °C and various GVL concentrations (0–75 vol%) for the production of biofuels and value-added biochemicals. Increasing GVL addition tunes glucose decomposition from isomerization into fructose and mannose to dehydration into 5-hydroxymethylfurfural (5-HMF) and levoglucosan (LGA). Particularly, direct dehydration of glucose to 5-HMF is found to be a primary reaction during glucose decomposition in HCGW. With the GVL concentration increasing from 1 to 75%, the selectivities of dehydration reactions to 5-HMF and LGA at 175 °C increase from 22 and 12% to 30 and 33%, respectively, while the selectivity of isomerization reaction to fructose at 175 °C decreases from 46 to 20%. Kinetic analysis indicates that glucose decomposition in HCGW follows first-order reaction kinetics. Further analysis shows that the reaction rate constants of dehydration reactions almost increase linearly with the GVL concentration, while those of isomerization reactions almost decrease linearly with the GVL concentration. The activation energy of glucose decomposition in HCGW also reduces slightly from 117 kJ/mol in water to 96 kJ/mol in 75% GVL. This study demonstrates that GVL/water co-solvent is effective to tune the glucose decomposition reaction for the production of biofuels and value-added biochemicals.